Taboos, food avoidances, and diseases: Local epistemologies of health among Coastal Endenese in Eastern Indonesia - Ramenzoni, Victoria Constanza (Frontiers in Sustainable Food Systems, 2023)
To advance interventions targeting malnutrition among small-scale fishing societies, knowledge on the role played by taboos and dietary avoidances on the consumption of fish related products becomes crucial. The article builds upon ethnographic fieldwork (participant observation, focus groups and interviews), dietary questionnaires (n: 112), and archival research among Coastal Endenese in Eastern Indonesia to understand the role played by taboos and dietary preferences in regulating intake of marine products. Moving beyond binary notions of “good” and “bad” when considering the food-system implications of taboos, it explores how local beliefs about illness and food shape dietary practices that can have concrete consequences for an individual's health. Endenese consider fish as having originated from terrestrial creatures, creating a continuous cycle of movement from land to sea and back. Within this cosmology, food is seen as a medium that can bring about healthy outcomes but also disease. Results emphasize the need to understand taboos and food avoidances within the larger cosmological and religious system but also underscore the changing nature of dietary preferences and values due to market integration processes which may have long-term repercussions on health. This information is key to the design of culturally sensitive dietary strategies and alternative livelihoods approaches that seek to minimize poverty.